Better diagnostic accuracy for GERD observed with the new MNBI cutoff: an observational study in Vietnam - Hang Dao Viet; Hue Luu Thi Minh; Long Hoang Bao; Phuong Do Nhat; Long Dao Van (BMC Gastroenterology)
Abstract Background Mean nocturnal baseline impedance (MNBI) is a novel metric for multichannel ambulatory impedance and pH (MI-pH) monitoring used to diagnose gastroesophageal reflux disease (GERD); however, its thresholds vary among different geographic areas and measuring systems. This study analyzed MI-pH data from Vietnamese patients to assess the diagnostic utility of novel MNBI thresholds in identifying GERD. Methods This retrospective study included 133 patients suspected of having GERD who underwent upper gastrointestinal endoscopy, esophageal high-resolution manometry (HRM) and 24-hour MI-pH monitoring (Laborie). The subjects were divided into 3 groups based on the acid exposure time (AET) index (abnormal, inconclusive and normal AET). The mean MNBI and the prevalence of abnormal MNBI values were compared within groups, and the diagnostic accuracy of this index for diagnosing GERD was evaluated via receiver operating characteristic (ROC) curves and their area under the curve (AUC). Results MNBI was significantly lower in patients with abnormal AET. The prevalence of MNBI < 2292 Ohms and MNBI < 1500 Ohms were greater in patients with abnormal AET (91.2% and 79.4%, respectively). The percentage of MNBI > 2500 Ohms was 44.4% in patients with normal AET but only 2.9% in patients with abnormal AET. MNBI had the highest AUC in discriminating abnormal AET (0.90, p < 0.001) in comparison with other metrics on MI-pH monitoring. The new cutoff value of 1500 Ohms had lower sensitivity but higher specificity than the previous threshold of 2292 Ohms. A multivariable regression analysis revealed that an MNBI < 1500 Ohms and total number of reflux events > 80/day were significantly associated with abnormal AET (> 6%). Conclusions Among Vietnamese patients with suspected GERD, the new MNBI cutoff of > 1500 Ohms had high sensitivity and specificity in diagnosing GERD, while the cutoff of 2500 Ohms could rule out this disease.